PELATIHAN DAN WORKSHOP MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY PADA GURU MGMP - Suherman . (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematics  is  a  compulsory  subject  at  primary  and  secondary  education levels in Indonesia. However, several studies have concluded that mathematics is one of the subjects that students are less interested in. The low interest of students is due to the fact that most mathematics teachers still use conventional learning media in mathematics learning, especially in geometry. This happens due to the lack of teacher's ability to apply technology in mathematics learning, especially in geometry lessons. One effort that can be done is through community service aimed at Junior High School Mathematics teachers who  are  members  of  the  Junior  High  School  Mathematics  MGMP  in  Limapuluh  Kota Regency.  The  activity  of  developing  learning  tools  was  made  in  two  stages,  namely designing and building AR applications using Unity 3D. The modeling process uses the Blender application. Whereas Vuforia SDK to form AR and playmaker as programming. This  application  has  three  main  features  in  the  form  of  building  material,  tutorials,  and application guides. As an output, the user can provide input and the system will read the program according to the markers provided separately from the application. Based on the results of devotion activities that have been carried out it is concluded that digital props based  on  Augmented  reality  have  been  successfully  made  and  help  learning  in  the material of building.Keywords — through community service, Augmented reality, Blender application